A Comprehensive Guide to Root Canal Treatment - Chatterjee, Srishti Songsoya; Govind, Shashirekha (Journal of Biomedical and Pharmaceutical Research, 2024)
Traditional protocols involve cleaning the pulp chamber and root canals and removing the bacteria and the smear layer. Several globular and non-globular dentine types are revealed when the smear layer is removed. The dentinal walls should be cleaned before the lumen is chemically or mechanically enlarged. Apexogenesis and apexification are the sources of emerging pulp therapies that use totipotent, multipotent, or unipotent stem cells to help regenerate the tooth pulp. Keywords: Root Canal Treatment, Contemporary techniques, Benefits of RCT